The development of the system of government in the civilizations of Mesopotamia and southern Arabia - Baji, Majeed (Al-Adab Journal, 2025)
The civilizations of Mesopotamia and South Arabia witnessed the development of systems of government throughout the ages. It started with a religious monarchy, as the ruler was considered an intermediary between the people and the gods. Then It moved to strong centralized monarchies, such as Sargon of Akkad, and Urnammu and Hammurabi, up to the Assyrian kings, as for the systems of government in southern Arabia, despite its chronological lag from Mesopotamia, developed its own a system of its own, initially based on the customs of the and was soon influenced by Mesopotamia, establishing kingdoms with a centralized system of government These systems were influenced by geographical and economic conditions, and emerged different types of administrative and legal organization.